Prediabetes Induced by a Single Autoimmune B Cell Clone - Phillips, Nathaniel; Ke, Eugene; Nham, Amy; Seidl, Maximilian; Freeman, Brent; Abadejos, Justin R.; Xiao, Changchun; Nemazee, David; Ku, Manching; Kirak, Oktay (Frontiers in Immunology, 2020)
While B cells play an important role in the onset of type-1 diabetes (T1D), little is know about their role in those early stages. Thus, to gain new insights into the role of B cells in T1D, we converted a physiological early pancreas-infiltrating B cell into a novel BCR mouse model using Somatic Cell Nuclear Transfer (SCNT). Strikingly, SCNT-derived B1411 model displayed neither developmental block nor anergy. Instead, B1411 underwent spontaneous germinal center reactions. Without T cell help, B1411-Rag1-/- was capable of infiltrating the pancreas, forming tertiary lymphoid follicles and undergoing class-switching. RNA-Seq analysis identified 93 differentially expressed genes in B1411 compared to WT B cells, including Irf7, Usp18 and Mda5 that had been linked to a potential viral etiology of T1D. We also found various members of the oligoadenylate synthase (OAS) family to be enriched in B1411, such as Oas1, which had recently also been linked to T1D. Strikingly, when challenged with glucose B1411-Rag1-/- mice displayed impaired glucose tolerance.